Macroeconomic effects of a 10% cut in statutory marginal income tax rates on ordinary income - Jason DeBacker; Richard W. Evans; Kerk L. Phillips (American Enterprise Institute (AEI), 2015)
This paper integrates a microsimulation (partial equilibrium) model of tax policy with a dynamic scoring approach to tax policy analysis using a dynamic general equilibrium macroeconomic model. Both approaches have strengths and weaknesses. Our integration of the two models combines the strength of both approaches to give tax revenue estimates based on the rich heterogeneity, realistic demographics, and many tax levers from the microsimulation model as well as dynamic model estimates that account for the effects of tax changes on macroeconomic variables.
Keywords: A; 330; Economic growth; income tax; tax cuts